Contralateral lateral rectus muscle recession in patients with Duane retraction syndrome type 3 - Snir, M (Nature Publishing Group, 2014)
AIMS: The aim of this study was to evaluate the motor, sensory, functional, and head posture results of recession of the lateral rectus muscle contralateral to the involved eye in patients with exotropic Duane retraction syndrome (DRS) type 3. METHODS: This was a retrospective, longitudinal, observational study of a consecutive clinical case series. Of the 11 patients with DRS type 3 operated on at a tertiary medical center from 1977 to 2012, 8 underwent recession of the lateral rectus muscle contralateral to the involved eye (with combined Y-splitting of ipsilateral lateral rectus muscle in 3 of them). Full ophthalmic, orthoptic, and neurological examination was performed before and after surgery. Main outcome measures included intragroup changes in motor misalignment, abnormal head turn, ocular upshoot, and stereopsis. RESULTS: Mean patient age was 8.75±3.1 years at surgery. Mean exodeviation for distance was −17.3±3.5 prism diopters (PD) preoperatively and −4.0±6.1 PD postoperatively; corresponding values for near were −23.1±7.2 PD and −5.9±8.7 PD. Motor deviation improved by 77% for distance (P=0.017) and 74.5% for near (P=0.01). In 7/8 patients, the postoperative residual exodeviation (distance and near) was <8.0 PD. There was an 80% improvement in head turn, from 15.3±4° before surgery to 3.1±5.0° after (P=0.01). Stereopsis improved significantly in 6/8 patients. Findings remained stable during follow-up (mean duration 35.9±50.8 months, range 5–132 months). CONCLUSIONS: Contralateral lateral rectus muscle recession appears to be a promising technique for the treatment of moderate unilateral DRS type 3, with patients showing significant motor and functional improvement and a decrease in head turn.